A catalogue of unusually long thermonuclear bursts on neutron stars. Issue 3 (2nd February 2023) - Alizai, K; Chenevez, J; Cumming, A; Degenaar, N; Falanga, M; Galloway, D K; in 't Zand, J J M; Jaisawal, G K; Keek, L; Kuulkers, E; Lampe, N; Schatz, H; et al.
ABSTRACT: Rare, energetic (long) thermonuclear (Type I) X-ray bursts are classified either as intermediate-duration or 'supern' bursts, based on their duration. Intermediate-duration bursts lasting a few to tens of minutes are thought to arise from the thermonuclear runaway of a relatively thick (≈10 10 g cm −2 ) helium layer, while superbursts lasting hours are attributed to the detonation of an underlying carbon layer. We present a catalogue of 84 long thermonuclear bursts from 40 low-mass X-ray binaries, and defined from a new set of criteria distinguishing them from the more frequent short bursts. The three criteria are: (1) a total energy release longer than 10 40 erg, (2) a photospheric radius expansion phase longer than 10 s, and (3) a burst time-scale longer than 70 s. This work is based on a comprehensive systematic analysis of 70 bursts found with INTEGRAL, RXTE, Swift, BeppoSAX, MAXI, and NICER, as well as 14 long bursts from the literature that were detected with earlier generations of X-ray instruments. For each burst, we measure its peak flux and fluence, which eventually allows us to confirm the distinction between intermediate-duration bursts and superbursts. Additionally, we list 18 bursts that only partially meet the above inclusion criteria, possibly bridging the gap between normal and intermediate-duration bursts. With this catalogue, we significantly increase the number of long-duration bursts included in the MINBAR and thereby provide a substantial sample of these rare X-ray bursts for further study.